EXPERT SYSTEM FOR DIAGNOSING DISEASES IN GOATS USING THE FORWARD CHAINING METHOD: CASE STUDY OF FARMS IN DERSOYONO VILLAGE, DAWE - Kasparova, Dita Yanuari; Listyorini, Tri; Supriyati, Endang (Tekmapro, 2025)
This research aims to design and implement an expert system supported by artificial intelligence to diagnose diseases in goats with the forward chaining method. The goal is to solve the problems faced by “Kertosono farm” located in Dawe village, Kudus district. This farm experiences obstacles such as difficult access to veterinarians due to long distances and lack of knowledge about initial treatment for their livestock. This system is designed to facilitate users in the treatment of their livestock, the knowledge in this expert system is limited to the information that has been inputted, including disease symptoms and first aid procedures. The diagnosis provided by the system is based on the rules and information that has been entered, not as a substitute for direct diagnosis by a veterinarian. Researchers use the forward chaining method which works more effectively by collecting information first before drawing conclusions from the data. This method speeds up the decision-making process, especially in situations that require a quick response, and is easy enough to implement in an expert system, so that the inference process becomes clearer. The system can immediately evaluate new information and apply relevant rules without having to repeat the entire initial data, and it is possible to track the inference steps taken, so that the user can understand how the conclusion was reached. Keywords: Forward Chaining, Expert System, Waterfall, Artificial Intelligence.